1998
DOI: 10.1105/tpc.10.4.613
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Lauroyl–Acyl Carrier Protein Thioesterase in Brassica napus Seeds Induces Pathways for Both Fatty Acid Oxidation and Biosynthesis and Implies a Set Point for Triacylglycerol Accumulation

Abstract: Expression of a California bay lauroyl-acyl carrier protein thioesterase (MCTE) in developing seeds of transgenic oilseed rape alters the fatty acid composition of the mature seed, resulting in up to 60 mol% of laurate in triacylglycerols. In this study, we examined the metabolism of lauric acid and 14 C-acetate in developing seeds of oilseed rape that express high levels of MCTE. Lauroyl-CoA oxidase activity but not palmitoyl-CoA oxidase activity was increased several-fold in developing seeds expressing MCTE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 26 publications
3
58
3
Order By: Relevance
“…The obligatory induction of b-oxidation and the glyoxylate cycle enzyme activities in leaves of these plants was a reasonable suggestion since levels in non-fatty tissues are much lower than in germinating seeds (Gerhardt 1983) and may not be capable of eciently degrading a large amount of medium-chain fatty acid. The recent report that MCOX activity was speci®cally induced in leaves of MCTE-expressing plants appeared to substantiate this conclusion (Eccleston and Ohlrogge 1998). The failure to accumulate an unusual fatty acid in leaves has also been observed for Arabidopsis plants engineered to produce ricinoleic acid (Broun et al 1998).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The obligatory induction of b-oxidation and the glyoxylate cycle enzyme activities in leaves of these plants was a reasonable suggestion since levels in non-fatty tissues are much lower than in germinating seeds (Gerhardt 1983) and may not be capable of eciently degrading a large amount of medium-chain fatty acid. The recent report that MCOX activity was speci®cally induced in leaves of MCTE-expressing plants appeared to substantiate this conclusion (Eccleston and Ohlrogge 1998). The failure to accumulate an unusual fatty acid in leaves has also been observed for Arabidopsis plants engineered to produce ricinoleic acid (Broun et al 1998).…”
Section: Discussionmentioning
confidence: 87%
“…The third explanation is that a post-transcriptional mechanism could result in higher levels of speci®c enzymes from pre-existing transcripts. This has been suggested to explain the increase in protein levels of fatty acid synthesis enzymes without a parallel increase in transcript levels in developing seeds of the transgenic B. napus producing lauric acid (Eccleston and Ohlrogge 1998). Unfortunately, in that study it was not possible to make the same conclusions for the fatty-acid-cataboliz ing enzymes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Total root tissue was collected from plants grown for 6 weeks in sealed tissue culture boxes containing 50 mL of growth media (1ϫ Murashige and Skoog salts, 1ϫ B vitamins, and 0.5% [w/v] agarose). Oilseed rape (Brassica napus cv 212/ 86, line 18) was grown in a green house (Eccleston and Ohlrogge, 1998). Seeds were collected from oilseed rape siliques 25 to 30 d after flowering and leaves were collected from the same plants of the same age.…”
Section: Plant Material Rna Extraction and Probe Synthesismentioning
confidence: 99%
“…We previously observed that high lauric acid production in transgenic canola induces b-oxidation pathways for lauric acid breakdown (Eccleston and Ohlrogge 1998). Thus, low levels of unusual monoene accumulation could be due to the breakdown of products from the introduced desaturases.…”
Section: Discussionmentioning
confidence: 98%